Two new species of the genus Apsidophora Diakonoff, 1973 (Lepidoptera: Tortricidae: Olethreutinae) from Thailand - Pinkaew, Nantasak; Muadsub, Sopita (Zootaxa, 2020)
Two new species, Apsidophora bala sp. nov. and Apsidophora chandrapatyae sp. nov., are described. Illustrations of adult and genitalia are provided. We also present a photograph of living specimen of A. chandrapatyae sp. nov. in natural resting posture. The two new taxa increase the number of described Apsidophora species to 3.